Evaluating the frequency of asymptomatic Ebola virus infection. (10th April 2017) - Mbala, Placide; Baguelin, Marc; Ngay, Ipos; Rosello, Alicia; Mulembakani, Prime; Demiris, Nikolaos; Edmunds, W. John; Muyembe, Jean-Jacques
Abstract : The potential for asymptomatic infection from Ebola viruses has long been questioned. Knowing the proportion of infections that are asymptomatic substantially changes the predictions made by mathematical models and alters the corresponding decisions based upon these models. To assess the degree of asymptomatic infection occurring during an Ebola virus disease (EVD) outbreak, we carried out a serological survey in the Djera district of the Equateur province of the Democratic Republic of the Congo affected by an Ebola outbreak in 2014. We sampled all asymptomatic residents ( n = 182) of 48 households where at least one case of EVD was detected. To control for potential background seroprevalence of Ebola antibodies in the population, we also sampled 188 individuals from 92 households in an unaffected area with a similar demographic background. We tested the sera collected for anti-Ebola IgG and IgM antibodies at four different dilutions. We then developed a mixture model to estimate the likely number of asymptomatic patients who developed IgM and IgG responses to Ebola antigens in both groups. While we detected an association between medium to high titres and age, we did not detect any evidence of increased asymptomatic infection in the individuals who resided in the same household as cases. This article is part of the themed issue 'The 2013–2016 West African Ebola epidemic: data, decision-making and disease control'.